PENGGUNAAN WHATSAPP GROUP DENGAN MEDIA POWERPOINT UNTUK MENINGKATKAN HASIL BELAJAR IPS MELALUI PETA RUPA BUMI SISWA KELAS IX SMP NEGERI 3 PRUBATUA - DOLLAR SIMATUPANG (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2022)
The purpose of this study is to determine the improvement of student learning outcomes after applying the use of whatsapp groups with powerpoint media in social studies learning material on the geographical conditions of the Asian continent and other continents through the Earth Map. The type of research is classroom action research with the stages of each cycle consisting of planning, action, observation and reflection. The subjects of the study were Class IX students of SMP Negeri 3 Purbatua for the academic year 2021/2022 with a total of 16 students. Techniques and data collection tools using test and non-test techniques (observations, interviews, and student worksheets). The data validation technique used triangulation technique. The data analysis method in this study used qualitative data analysis. The results showed that learning motivation showed an increase from 5 students or 31.25% in the initial study to 10 students or 62.50% in the first cycle and 16 students or 100% in the last cycle and the average increase in the initial study learning outcomes was 53 .75 in the first cycle the average score obtained by students was 62.50 and in the second cycle the average score obtained by students was 75.63 at the end of the second cycle and was supported by an increase in learning completeness in the initial state of 3 students (18, 75%), after the improvement with the use of whatsapp groups with powerpoint media in the first cycle increased to 7 students or 43.75% and in the second cycle increased again to 14 students or 87.50%. From the acquisition of the figures above, it can be concluded that in the second cycle, the process of implementing learning improvements was declared successful and completed in the second cycle. From the explanation above, it can be concluded that the use of Whatsapp Group with Powerpoint Media can improve the process and student learning outcomes. ABSTRAKTujuan dari penelitian ini yaitu untuk mengetahui peningkatan hasil belajar siswa setelah menerapkan penggunaan whatsapp group dengan media powerpoint dalam pembelajaran IPS Materi Kondisi Geografis Benua Asia dan Benua Lainnya melalui Peta Rupa Bumi. Jenis penelitian adalah penelitian tindakan kelas dengan tahapan setiap siklus terdiri dari perencanaan, tindakan, pengamatan dan refleksi. Subjek penelitian adalah siswa Kelas IX SMP Negeri 3 Purbatua Tahun Pelajaran 2021/2022 sebanyak 16 orang siswa. Teknik dan alat pengumpulan data menggunakan teknik tes dan nontes (observasi, wawancara, dan lembar kerja siswa). Teknik validasi data menggunakan teknik triangulasi. Metode analisis data dalam penelitian ini menggunakan analisis data kualitatif. Hasil penelitian menunjukkan bahwa motivasi belajar menunjukkan peningkatan dari 5 siswa atau 31,25% pada studi awal menjadi 10 siswa atau 62,50% pada siklus pertama dan 16 siswa atau 100% pada siklus terakhir dan kenaikan rata-rata hasil belajar studi awal sebesar 53,75 pada siklus I nilai rata-rata yang diperoleh siswa adalah 62,50 dan pada siklus II rata-rata nilai yang diperoleh siswa adalah 75,63 pada akhir siklus kedua serta didukung dengan peningkatan ketuntasan belajar pada keadaan awal sebanyak 3 siswa (18,75%), setelah dilaksanakan perbaikan dengan penggunaan whatsapp group dengan media powerpoint pada siklus I meningkat menjadi 7 siswa atau 43,75% dan pada siklus II meningkat kembali menjadi 14 siswa atau 87,50%. Dari perolehan angka-angka di atas dapat disimpulan bahwa pada siklus kedua, proses pelaksanaan perbaikan pembelajaran dinyatakan berhasil dan tuntas pada siklus kedua. Dari penjelasan di atas dapat disimpulkan bahwa Penggunaan Whatsapp Group dengan Media Powerpoint dapat meningkatkan proses, hasil belajar siswa.